QUEST FOR SOCIAL, POLITICAL AND ECONOMIC IDENTITIES OF WOMEN IN SHASHI DESHPANDE’S THAT LONG SILENCE - Shamurailatpam Geeta Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The important step to women’s emancipation is the financial independence of women. The novel That Long Silence shows the need to have one’s income confined to both this elite class of women as well as women of lower class who do not have the opportunity to learn and educate themselves. The protagonist, Jaya could earn both fame and money by her regular column called “Seeta”. Maid servant Jeeja earns money and maintains her family when her husband gets remarried to another woman as she is barren. She is a thorough professional and dignity of labour. She feels proud of her work and manages to earn more than the other maids because of her “reputation of reliability”. Financial independence on women’s amelioration really helps to free them from their total dependence syndrome to a certain extent for achieving their goal in quest for Social, Political and the Economic identities.